2012
DOI: 10.1111/j.1752-1688.2012.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship Between Landscape Patterns and Nonpoint‐Source Pollution in the Danjiangkou Reservoir Basin in China1

Abstract: The constrained ordination method from quantitative ecology was utilized to assess the relationship between landscape patterns and nonpoint‐source (NPS) pollution for the purpose of identifying effective water‐quality improvement practices in Danjiangkou Reservoir (DJKR) basin, China. The soil and water assessment tool (SWAT) was applied to simulate NPS pollution and the Fragstats model was applied to calculate the landscape metrics. The study concluded that organic nutrients formed the main NPS pollutant in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Importantly, the rice growing season in this area extends from June to October each year which corresponds with the main rainy and hydrologically active period of the year. Therefore, Lalin River was vulnerable to pollution as paddy fields were characterized with the most intensive P runoff (Hao et al, 2012). As P runoff varied temporally, monitoring in field studies is usually costly and labor intensive, little information about P runoff from paddy fields is available in this region.…”
Section: Introductionmentioning
confidence: 98%
“…Importantly, the rice growing season in this area extends from June to October each year which corresponds with the main rainy and hydrologically active period of the year. Therefore, Lalin River was vulnerable to pollution as paddy fields were characterized with the most intensive P runoff (Hao et al, 2012). As P runoff varied temporally, monitoring in field studies is usually costly and labor intensive, little information about P runoff from paddy fields is available in this region.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, policies have been formulated to regulate this kind of LUCC. The following list shows a selection of Chinese policies as well as examples of studies conducted to show the impact of LUCC resulting from one of these programmes on the hydrological conditions: Grain‐for‐Green Programme, also known as Sloping Land Conversion Programme: implemented in 1999 by the Chinese government (Zhou et al ., : runoff and sediment; Deng et al ., : runoff and soil erosion; Long et al ., : soil erosion; Bieger et al ., : water balance and sediment transport; Wang et al ., : carbon) ‘Conversion of Cropland to Forest and Grassland Programme’: nationwide, adopted in 1999 (Qiu et al ., : soil water storage and evapotranspiration; Qiu et al ., : water budget) ‘Reforestation of Cultivated Land’ (RFCL): (Wang et al ., : water flow components, total sediment loading, nitrogen and phosphorus) ‘Returning Farmland to Forest’: since 1989 in the middle and lower reaches of the Yangtze River (Huang et al ., : surface runoff and soil loss) ‘Conversion Cropland to Forest Policy’: in China, especially in the middle and upper reaches of the Yangtze River (Ouyang et al ., : streamflow, sediment yields and main pollutants; Hao et al ., : pollutants and soil loss) ‘Mountain–River–Lake’ (MRL) Development Programme: in 1985 by the Jiangxi Provincial Government (Zhou et al ., : carbon dynamic) …”
Section: Introductionmentioning
confidence: 99%
“…Recent monitoring has shown that water quality standards are not fully compliant with the criteria specified by the Ministry of Environmental Protection in China. Specifically, the total nitrogen concentration of the water in the storage area of the Danjiangkou Dam failed to meet the standards required for a healthy water body (Hao et al 2012). The origin of the problem, these researchers conclude, is runoff from agricultural areas in the Danjiangkou Reservoir basin.…”
Section: Environmental and Ecological Challengesmentioning
confidence: 98%